The ocean's role in global change : progress of major research programs - Merrell, William (National Academy Press, 1994)
Provides summaries on the progress of the major oceanographic research programs. This book looks at programs that study processes that occur over periods ranging from days to hundreds of years - the contemporary system, and those that seek to understand long-term variations ranging from thousands to millions of years - the geological perspective.
Board chairman: William Merrell, Jr.
Work was sponsored by the National Oceanic and Atmospheric Administration's Office of Global Programs through the National Science Foundation grant no. OCE-9313563-R.
Keywords: Ocean-atmosphere interaction -- Research -- United States.; Interaction mer-atmosphère -- Recherche -- États-Unis.; SCIENCE -- Earth Sciences -- Oceanography.; NATURE -- Ecosystems & Habitats -- Oceans & Seas.; Ocean-atmosphere interaction -- Research; United States